Pogłoski o sprawie templariuszy - przepływ informacji w społeczeństwach Europy zachodniej na początku XIV wieku = The rumors about the templar case - the flow of information in Western Europe societies at the beginning of the 14th century - Satora, Magdalena (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The sudden arrests of the French Templars in October 1307 was a great surprise both to the most important participants of the political life of Western Europe and to the members of the order, which had played an important role on the courts of particular countries of this part of the continent and the papal curia for over two hundred years.
Keywords: Zakon Ubogich Rycerzy Chrystusa i Świątyni Salomona; templariusze; Europa; 14 w.